A randomized comparison on the corneal endothelial morphology after the use of 2 different viscoelastic agents during phacoemulsification surgery - Ismail, Shatriah; Ibrahim, Mohtar; Ghani, Zulkifli Abd (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2006)
Objective: To compare corneal endothelial morphological changes after the use of Healon 5 (sodium hyaluronate 2.3%) and Healon GV (sodium hyaluronate 1.4%) during phacoemulsification surgery, particularly at three months after the surgery. Settings: Department of Ophthalmology, School of Medical Sciences, Universiti Sains Malaysia, Malaysia and Eye clinic, Hospital Kota Bharu, Kelantan, Malaysia. Materials and Methods: One hundred and ten patients were randomized, 55 per group, in a prospective randomized clinical trial of phacoemulsification surgery using Heal on 5 or Heal on GV. Three ophthalmologists performed the surgeries. The corneal endothelial cells density, average cell size, coefficient variation and hexagonality were assessed preoperatively and at three months postoperatively using a non-contact specular microscope Topcon SP2000P. Analysis of the data was performed using SPSS version 10.0, Independent-Samples T Test. Results: There was statistically significant difference between Healon 5 group and Healon GV group based on endothelial cell density (p=0.015) and percentage of cell loss (p=0.033). The cell size was noted significantly smaller in the Healon 5 group compared to the Healon GV group at three months (p=0.004). A similar result was also noted in percentage of changes in cell size (p=0.033). There were no statistically significant differences in changes of coefficient variation of cell size and hexagonality in both groups at three months after the surgery. Conclusion: Minimal corneal endothelial morphological changes were noted in the Healon 5 group compared to the Healon GV group, particularly in term of less cell loss and less alteration in cell size at three months after the surgery. Thus, indicates that Healon 5 is more effective than Healon GV in minimizing risk of corneal endothelial injury during phacoemulsification surgery.